Advanced cardiac imaging in athlete`s heart: unravelling the grey zone between physiologic adaptation and pathology - Palmisano, A.; Darvizeh, F.; Cundari, G.; Rovere, G.; Ferrandino, G.; Nicoletti, V.; Cilia, F.; de Vizio, S.; Palumbo, R.; Esposito, A.; Francone, M. (La radiologia medica, 2021)
Over the last decades, interest toward athlete`s heart has progressively increased, leading to improve the knowledge on exercise-induced heart modifications. Sport may act as a trigger for life-threatening arrhythmias in patients with structural or electrical abnormalities, hence requiring to improve the diagnostic capability to differentiate physiological from pathological remodeling. Pathological alterations are often subtle at the initial stages; therefore, the challenge is to promptly identify athletes at risk of sudden cardiac death during the pre-participation screening protocols. Advanced imaging modalities such as coronary computed tomography angiography (CCTA) and cardiac magnetic resonance (CMR) can non-invasively depict coronary vessels and provide a deep morpho-functional and structural characterization of the myocardium, in order to rule out pathological life threatening alterations, which may overlap with athletes` heart remodeling. The purpose of the present narrative review is to provide an overview of most frequent diagnostic challenges, defining the boundaries between athlete's heart remodeling and pathological structural alteration with a focus on the role and importance of CCTA and CMR.